PENGARUH FAKTOR-FAKTOR LINGKUNGAN TERHADAP TINGKAT KEKRITISAN DAERAH RESAPAN DI SUB DAS AEK SILANG DAERAH ALIRAN SUNGAI DANAU TIBA (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2017)
Recharge areas was instrumental in arranging water transportation system, therefore has the ability to control surface water to absorb water into the ground so that it can overcome the problem of flooding and drought. Conditions recharge areas greatly affected by the climate (rainfall), soil type, slope and land use types. The research objective was to assess the effect of environmental factors on the critical level of recharge areas and efforts to rehabilitate the recharge areas. Analysis method using valuation techniques critically recharge areas through overlaying maps of slope, soil type, rainfall and land use types in which each map beforehand transformed into map form infiltration. Classification potential criticality ratings recharge areas in the top six classes, namely good, normal naturally, potential critical, fairly critical, critical and very critical. The results show the criticality classification recharge areas in the Aek Silang sub watershed there are four classes, namely good, normal naturally, potential critical and fairly critical. Recharge areas be rehabilitated is a potential critical and fairly critical start with an area of each ​​7607.94 ha (38.40%) and 1384.63 ha (6.99%). Environmental factor that is possible to do the rehabilitation effort is a land use factor, since this factor is more influenced by aspects of human activity, while factors of slope, soil type and rainfall is difficult to control because it is natural. Efforts to rehabilitate both vegetatively and civil technically should be adapted to the physical condition of the land, land capability and suitability.